2010
DOI: 10.1016/j.cbi.2009.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology of human benzene exposure

Abstract: Toxicogenomic studies, including genome-wide analyses of susceptibility genes (genomics), gene expression (transcriptomics), protein expression (proteomics), and epigenetic modifications (epigenomics), of human populations exposed to benzene are crucial to understanding gene-environment interactions, providing the ability to develop biomarkers of exposure, early effect and susceptibility. Comprehensive analysis of these toxicogenomic and epigenomic profiles by bioinformatics in the context of phenotypic endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 52 publications
(52 reference statements)
3
58
0
1
Order By: Relevance
“…Under conditions prevailing at the workplace, benzene is absorbed by inhalation, although dermal absorption of liquid benzene is also significant [2]. Benzene metabolism has been extensively studied in various animal models, in vitro incubations, and by theoretical calculations [2][3][4][5][6][7], with evidences that it is impossible to distinguish between occupational and environmental exposure when the benzene level in the workplace is less than 100 μg/m 3 [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under conditions prevailing at the workplace, benzene is absorbed by inhalation, although dermal absorption of liquid benzene is also significant [2]. Benzene metabolism has been extensively studied in various animal models, in vitro incubations, and by theoretical calculations [2][3][4][5][6][7], with evidences that it is impossible to distinguish between occupational and environmental exposure when the benzene level in the workplace is less than 100 μg/m 3 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chronic exposure to benzene can cause fatigue, nervousness, irritability, blurred vision, and labored breathing. Repeated skin contact can cause redness, blistering, and scaly dermatitis [2,4,5]. Recent studies showed significant hematological disorders, chromosomal aberrations as well as relatively high concentration of phenol in 24-hour urine samples due to exposure to benzene in chemical industry workers [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollution Globally Decreased [199] Affected [207] Affected [211] Other Chemicals Benzene Affected [200] Increased Phosphorylation [208] Affected [216] Bisphenol A Globally Decreased [201] Increased Trimethylation [209] Affected [217] Ning et al Page 34 Table 3 Summary of Next-Generation Sequencing Platforms …”
Section: Dna Methylation Histone Modification Ncrna Expressionmentioning
confidence: 99%
“…Certainly, there have been success stories, for example: the human papillomavirus-cervical cancer association [Schiffman et al, 2007], the underpinning of the mechanism of action of certain chemical carcinogens (e.g., benzene, formaldehyde) [Zhang et al, 2010;IARC Monographs, 1995;Lan et al, 2004], the reduction in exposure misclassification (e.g., aflatoxin exposure and hepatocellular carcinoma) [Ross et al, 1992], and the identification of susceptibility factors through functional assays (e.g., chromosomal aberration, micronucleus assay) [Hagmar et al, 1998;Bonassi et al, 2007]. However, even with these advances many of the environmental factors that modify disease susceptibility remain elusive.…”
Section: From Molecular Epidemiology Of Traditional Biomarkers To Omimentioning
confidence: 99%